Autism spectrum disorder causes, mechanisms, and treatments: focus on neuronal synapses - Won, Hyejung; Mah, Won; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2013)
Autism spectrum disorder (ASD) is a group of developmental disabilities characterized by impairments in social interaction and communication and restricted and repetitive inter-ests/behaviors. Advances in human genomics have identified a large number of genetic varia-tions associated with ASD. These associations are being rapidly verified by a growing number of studies using a variety of approaches, including mouse genetics. These studies have also identified key mechanisms underlying the pathogenesis of ASD, many of which involve synaptic dysfunctions, and have investigated novel, mechanism-based therapeutic strategies. This review will try to integrate these three key aspects of ASD research: human genetics, animal models, and potential treatments. Continued efforts in this direction should ultimately reveal core mechanisms that account for a larger fraction of ASD cases and identify neural mechanisms associated with specific ASD symptoms, providing important clues to efficient ASD treatment.